Molecular characterization of the progenetic metacercariae crocodilicola pseudostoma parasitizing rhamdia quelen (Siluriformes, heptapteridae) in Brazil - Negrelli, Débora C. [UNESP]; Vieira, Diego H. M. D. [UNESP]; Abdallah, Vanessa D.; Azevedo, Rodney K. (FapUNIFESP (SciELO), 2020)
The trematodes have developed several adaptations and strategies to complete their life cycle in the intermediate host, without even reaching the definitive host. Thus, metacercariae through progeny can produce viable eggs by self-fertilization in the second intermediate host. We analyzed 30 specimens of Rhamdia quelen Quoy & Gaimard 1824 (Siluriformes, Heptapteridae) collected in the Jacaré-Pepira River, Ibitinga. Among the specimens analyzed, only one host was parasitized by the progenetic metacercariae of Crocodilicola pseudostoma Willemoes-Suhm 1870 (Digenea: Proterodiplostomidae) presenting prevalence of 3.3%, mean intensity of 68.0 ± 12.4 and mean abundance of 2.3 ± 0.4. This is the first record of progenesis in the metacercariae of C. pseudostoma in the Jacaré-Pepira River, as well as the first partial sequence of COI gene obtained from this species in Brazil.
Keywords: Biodiversity; Digenea; Proterodiplostomidae; Siluriformes